TEACHER DIFFICULTIES IN APPLYING SCIENCE LEARNING ENVIRONMENTAL MATERIALS BASED ON LOCAL WISDOM IN PRIMARY SCHOOLS - Hendi Susanto; Mu’jizatin Fadiana (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2025)
Abstract: The aim of this research is to describe teachers' difficulties in implementing environmentalscience learning based on local wisdom at MI Nurul Huda Ketambul Palang Tuban, East Java.. The researchmethod used is a qualitative descriptive research design. Data collection techniques are interviews,observation and documentation. The subjects of this research were 1 teachers and 21 students. Based on theresearch results, it shows that teachers still experience difficulties in the planning, implementation andevaluation processes. The difficulties experienced by teachers are a lack of training in making teachingmodules based on local wisdom which results in teachers not understanding how to relate the material tothe surrounding environment, a lack of learning time if all lessons are carried out using learning based onlocal wisdom because the school has to achieve learning material targets, students are too active whenstudying outside the classroom, and the students' sentences are less structured so it is difficult for the teacherto evaluate. So the solution to overcome this problem is to take part in training to improve the teacher'sability to carry out learning.Keywords: teacher difficulty, science learning, local wisdom, elementary school.